Upaya Meningkatkan Hasil Belajar IPS Melalui Metode Pembelajaran Problem Based Learning - Marditir Marpaung (JURNAL GLOBAL EDUKASI, 2017)
Abstract: The purpose of this study is to improve the learning outcomes in reading the map on the IPS learning materials local environmental maps through the method of Problem Based Learning. Subjects in this study were the fourth graders of SD Negeri 013848 Gedangan kec. Pulo Bandring TP. 2016/2017. The learning outcomes in cycle I reached an average value of 78.83 after cycle II, reflecting an average value of 87.5. The completeness of classical learning in the first cycle was achieved by 81.83% then in the second cycle there was an increase to 87.87%. Can summarize the use of Problem Based Learning mtode can improve student learning outcomes in reading the map on IPS learning materials local environmental maps through the method of Problem Based Learning. Keywords: guidance, reward, punishment Abstrak: Tujuan penelitian ini adalah untuk meningkatkan hasil belajar dalam membaca peta pada pembelajaran IPS materi peta lingkungan setempat melalui metode Problem Based Learning. Subjek dalam penelitian ini adalah siswa kelas IV SD Negeri 013848 Gedangan kec. Pulo Bandring TP. 2016/2017. Hasil belajar pada siklus I mencapai nilai rata-rata 78,83 setelah siklus II, refleksi nilai rata-rata mencapai 87,5. Ketuntasan belajar klasikal pada siklus I dicapai sebesar 81,83% selanjutnya pada sklus II terjadi peningkatan menjadi 87,87%. Dapat simpulkan penggunaan mtode Problem Based Learning dapat meningkatkan hasil belajar siswa dalam membaca peta pada pembelajaran IPS materi peta lingkungan setempat melalui metode Problem Based Learning. Kata kunci: problem based jearning, peta, lingkungan